Experimental the Influence of Growth Solution on Zinc Oxide Crystal Structures via Hydrothermal Method - Nasha Emieza Ruhaizat; Ainuddin, Ainun Rahmahwati; Zakiah Kamdi (International Journal of Integrated Engineering, 2020)
The properties of Zinc Oxide (ZnO) such as broad direct band gap (3.37eV), good crystallinity and inexpensive materials had gain interest of many researchers. This project is prone to investigate the role of growth solution in the formation of ZnO structures. The objective of this project is to growth the ZnO hexagonal rods structure on the seed layer coated glass substrate and to investigate the influence of ZNH and HMT precursor on structural and morphological properties by varying its molar ratio. Firstly, the ZnO were coated on the microscope glass substrate for five layers using sol gel spin coating techniques. The dimension of the microscope glass substrate used were 2.5cm x 2.5cm. The ZnO seed layer coated substrates then undergo low cost hydrothermal method for the growth of ZnO structures. Different concentration of ZNH:HMT growth solution were used during hydrothermal method at molar ratio 1:1, 1:2 and 2:1 so that the influence of HMT and ZNH in the formation of ZnO structures can be further investigate. Several types of machine were used for the characterization properties of ZnO structures such as X-ray diffraction spectrophotometer (XRD), field emission scanning electron microscopy (FESEM), and energy dispersive x-ray spectroscopy (EDS). XRD analysis revealed that the ZnO samples exhibited hexagonal rods structure. The higher concentration of HMT shows higher intensity of diffraction peaks at the plane (101), (100) and (002) of ZnO structures. FESEM images showed that uneven size of ZnO structure at higher ZNH concentration while large size of ZnO structures can be seen at higher HMT concentration. EDS proved that the elemental composition of Zn and O do exist in the sample.